2021
DOI: 10.3389/fcell.2021.733627
|View full text |Cite
|
Sign up to set email alerts
|

Pre-metastatic Niche Formation in Different Organs Induced by Tumor Extracellular Vesicles

Abstract: Primary tumors selectively modify the microenvironment of distant organs such as the lung, liver, brain, bone marrow, and lymph nodes to facilitate metastasis. This supportive metastatic microenvironment in distant organs was termed the pre-metastatic niche (PMN) that is characterized by increased vascular permeability, extracellular matrix remodeling, bone marrow-derived cells recruitment, angiogenesis, and immunosuppression. Extracellular vesicles (EVs) are a group of cell-derived membranous structures that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 74 publications
0
42
0
Order By: Relevance
“…Remodeling of the ECM, driven by proteolytic enzymes (such as matrix metalloproteinases) [ 2 ], by enzymes that control the modification and cross-linking of extracellular matrix proteins (such as lysyloxidases (LOX)) [ 3 ], results in increased stiffness and altered ECM composition. Tumor cells also secrete extracellular vesicles with nucleic acids, lipids and proteins, which can participate in tumor progression and behavior, including tumor environment remodeling, fibroblast activation, angiogenesis, immunomodulation or the establishment of pre-metastatic niches [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remodeling of the ECM, driven by proteolytic enzymes (such as matrix metalloproteinases) [ 2 ], by enzymes that control the modification and cross-linking of extracellular matrix proteins (such as lysyloxidases (LOX)) [ 3 ], results in increased stiffness and altered ECM composition. Tumor cells also secrete extracellular vesicles with nucleic acids, lipids and proteins, which can participate in tumor progression and behavior, including tumor environment remodeling, fibroblast activation, angiogenesis, immunomodulation or the establishment of pre-metastatic niches [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key factors that control CTC acceptance and possible micrometastasis formation is induction and stimulation of the supportive microenvironment (called premetastatic niche [263]) in distance organs by primary tumour [264]. Tumour cells display an ability to selectively modify the microenvironment of distant organs via extracellular vehicles (e.g., exomes).…”
Section: Effect Of Curcumin and Flavonoid Applications On Emt And Metastasis Formationmentioning
confidence: 99%
“…Numerous high-impact studies imply that tumour exosomes strongly support tumourgenesis and metastatic formation [264]. Ma et al reported that exosomes isolated from NSCLC patients displayed significantly higher levels of some miRNAs (e.g., miR-3157-3p, miR-3613-5p, and miR-3921) against healthy controls [266].…”
Section: Effect Of Curcumin and Flavonoid Applications On Emt And Metastasis Formationmentioning
confidence: 99%
“…Mexo secreted by highly metastatic melanoma cells are able to recruit bone marrow progenitor cells toward a pro-vasculogenic phenotype in the metastatic niche, mainly through MET signalling [ 95 , 96 , 97 ]. Therefore, we can hypothesize that Mexo initially promote angiogenesis to sustain tumour, then migrate to secondary sites to initiate PMN, to finally promote invasion and metastatic colonization to distant sites [ 98 ] ( Figure 2 ). Similar roles could be hypothesized also for acidic and hypoxic Mexo.…”
Section: How Acidity and Hypoxia Modulate Melanoma Progression Through Mexomentioning
confidence: 99%